A comparison of the Miller laryngoscope versus the prototype neonatal offset‐blade laryngoscope in a manikin. (18th December 2015) - Doreswamy, S. M.; Fusch, C.; Selvaganapathy, R.; Matharoo, H.; Shivananda, S.
Summary: Laryngoscope blades used to intubate newborn babies are relatively bulky and frequently exert high pressure on the upper jaw. We tested a prototype neonatal offset‐blade laryngoscope (NOBL) developed to overcome these limitations. Our aims were to compare the pressure on the upper jaw exerted by a size 0 Miller laryngoscope and the NOBL on a neonatal manikin, as well as the time taken to intubate the trachea and the area of view of the larynx. Twenty healthcare professionals with more than five years of experience in neonatal intensive care took part; the findings were assessed using pressure‐sensitive film and photographs. High‐pressure indentation occurred in 17 (85%) attempts using the Miller versus 1 (5%) using the NOBL (p = 0.0001). The median (IQR [range]) pressure exerted with the Miller laryngoscope was 455 (350–526 [75–650]) kPa vs 80 (0–133 [0–195]) kPa with the NOBL (p < 0.0001). The area of pressure exerted with the Miller laryngoscope was 68 (32–82 [0–110]) mm 2 vs 8 (0–23 [0–40]) mm 2 with the NOBL (p < 0.0001). The time to intubate was 8.3 (7.3–10.1[4–19]) s for the Miller and 8.0 (5.6–9.6 [4–13.5]) s for the NOBL (p < 0.0001). The area of view blocked by the Miller laryngoscope was 38% of the oral orifice versus 12% with the NOBL. We conclude that the NOBL significantly reduced undesired pressure on the upper jaw during tracheal intubation and improved the view of the larynx compared with a conventional laryngoscope.